Association between anlotinib trough plasma concentration and treatment outcomes in advanced non-small-cell lung cancer - Chen, Ling; Jiang, Hong; Rao, Jun-jie; Wang, Liu-sheng; Yan, Wei; Ye, Jian; Lou, Jiang (Frontiers in Oncology, 2023)
Background Efficacy and toxicities of anlotinib (ANL) show large inter-patient variation, which may partly be explained by differences in ANL exposure. Exposure-response/toxicities relationship have not been investigated for ANL. Therefore, the aim of the present study was to explore the association between the trough plasma concentration (Ctrough) of ANL and treatment outcomes in Chinese patients with advanced non-small cell lung cancer (NSCLC). Methods Patients with advanced NSCLC who started third-line or further ANL alone therapy between January 2021 and October 2022. This study examined the ANL Ctrough and clinical response evaluation at day 43 after initiation of ANL treatment. We evaluated the association between the ANL Ctrough and clinical efficacy and toxicities. Additionally, this study defined patients with complete response (CR), partial response (PR) and stable disease (SD) as responder. The receiver-operating characteristic (ROC) curve combined with Youden index was identify the potential threshold value of ANL Ctrough for the responder. Results 52 patients were evaluated for analyses. The median ANL Ctrough was 11.45ng/ml (range, 3.69-26.36 ng/ml). The ANL Ctrough values in the PR group (n=6, 15.51 ng/ml (range, 8.19-17.37 ng/ml)) was significantly higher than in the PD group (n=8, 7.44 ng/ml (range, 5.41-14.69 ng/ml), p=0.001). The area under the ROC curve (AUCROC) was 0.76 (95% confidence interval (CI), 0.58-0.93; p=0.022) and threshold value of ANL Ctrough predicting responder was 10.29 ng/ml (sensitivity 65.9% and specificity 87.5%, the best Youden index was 0.53). The disease control rate (DCR) was 84.6%, and DCR was significantly higher in the high-exposure group (≥10.29ng/ml) than low-exposure group (<10.29ng/ml) (96.67% vs 68.18%, p=0.005). Although there was no significant difference in ANL Ctrough between grade ≥ 3 and grade ≤2 toxicities, the incidence of any grade hand-foot syndrome (70.0% vs 36.36%, p=0.016) and thyroid-stimulating hormone elevation (53.33% vs 22.73%, p =0.026) was significantly higher in the high-exposure group compared with the low-exposure group. Conclusions Considering these results, we propose that maintaining ANL Ctrough ≥ 10.29ng/ml was important for achieving the response in advanced NSCLC patients treated with ANL.